Determinação de elementos-traço em borracha natural e de silicone por espectrometria de absorção atômica com forno de grafite com amostragem de sólidos - Bartz, Fabiane Regina (2012)
In this work the use of solid sampling graphite furnace atomic absorption spectrometry for the determination of Cr, Cu, Mn, Ni, Pb, Sb, Sn and Zn in natural rubber and Cr in silicone rubber was proposed. Calibration was carried out with reference solutions. For natural rubber, a deuterium background correction system was used and no chemical modifier was necessary for the elements determination. For Cr determination in silicone rubber, Mg was used as chemical modifier and background correction based on Zeeman-effect was necessary. The accuracy was checked by comparing the results obtained by the proposed method with those obtained by inductively coupled plasma mass spectrometry, in this case after wet decomposition of the sample in closed vessels (a natural rubber sample was also analyzed by neutron activation analysis). Results were in agreement for most of samples and elements. Up to 5 and 1 mg of natural and silicone rubber, respectively, could be introduced in the atomizer. The limits of detection was 6.0, 2.8, 9.0, 0.45, 1.3, 6.0, 8.0 e 0.17 ng g-1 for Cr, Cu, Ni, Mn, Pb, Sb, Sn and Zn, respectively, in natural rubber and 29 ng g-1 for Cr in silicone rubber. The relative standard deviation was lower than 17% for natural rubber and lower than 20% for silicone rubber.